2021
DOI: 10.32942/osf.io/ze8ty
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Species comparison of among- and within-individual variation and correlations

Abstract: Individuals frequently differ consistently from one another in their average behaviors (i.e. “animal personality”) and in correlated suites of consistent behavioral responses (i.e. “behavioral syndromes”). However, understanding the evolutionary basis of this (co)variation has lagged behind demonstrations of its presence. This lag partially stems from comparative methods rarely being used in the field. Consequently, much of the research on animal personality has relied on “adaptive stories” focused on single s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…derived and ancestral population designations should be confirmed). Phylogenetic analysis may also provide a useful framework to identify potentially vestigial forms of behaviour, as well as identifying behavioural variation associated with phylogenetic signal more generally, which recent research has indicated might account for a substantial proportion of observed variation (Dalos et al ., 2021; but see White, Pascall & Wilson, 2020). Selection pressures at the relevant time points should also where possible be corroborated – for example by historical record, metagenomics or geological/fossil records (Cousyn et al ., 2001) – rather than by assuming that contemporary differences in selection regime are representative of long‐term trends.…”
Section: Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…derived and ancestral population designations should be confirmed). Phylogenetic analysis may also provide a useful framework to identify potentially vestigial forms of behaviour, as well as identifying behavioural variation associated with phylogenetic signal more generally, which recent research has indicated might account for a substantial proportion of observed variation (Dalos et al ., 2021; but see White, Pascall & Wilson, 2020). Selection pressures at the relevant time points should also where possible be corroborated – for example by historical record, metagenomics or geological/fossil records (Cousyn et al ., 2001) – rather than by assuming that contemporary differences in selection regime are representative of long‐term trends.…”
Section: Future Researchmentioning
confidence: 99%
“…They also warrant consideration in behavioural research. Vestigial behaviours might re‐emerge under artificial experimental conditions, and may be prone to misinterpretation by researchers seeking to understand behavioural variation within an adaptive context (Gould & Lewontin, 1979; Dalos et al ., 2021). For example, Byers (1997) controversially argued that many behavioural and morphological adaptations of American pronghorn ( Antilocapra americana ) populations are in fact adaptations to so‐called ‘ghosts of predators past’, that is, predators that have been long extinct (see also Peckarsky & Penton, 1988).…”
Section: Introductionmentioning
confidence: 99%